The challenge of fifth generation R&D - Rogers, Debra M. Amidon (Research management (Now: research technology management))
Debra M. Amidon Rogers calls for innovation systems that optimize knowledge (not information) flows through networks that include customers, suppliers, distributors and other stakeholders.